2014
DOI: 10.1111/pace.12394
|View full text |Cite
|
Sign up to set email alerts
|

The Retrograde P‐Wave Theory: Explaining ST Segment Depression in Supraventricular Tachycardia by Retrograde AV Node Conduction

Abstract: STd during SVT is observed at long VA intervals when the retrograde P wave matches the ST segment, without dependence on the TCL. This suggests that STd is not necessarily rate dependent but a result of a fusion between the ST segment and the P wave.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…Some previous studies have reported a correlation between ST depression during supraventricular tachycardia and heart rate, while some others did not . In our study, patients with ST‐segment depression had a higher arrhythmic rate ( p = 0.044).…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Some previous studies have reported a correlation between ST depression during supraventricular tachycardia and heart rate, while some others did not . In our study, patients with ST‐segment depression had a higher arrhythmic rate ( p = 0.044).…”
Section: Discussioncontrasting
confidence: 64%
“…Other possible theories concerning the development of ST depression during these arrhythmias are worthy of consideration. They include the fusion of retrograde P wave and ST segment, increased total atrial activation time and ventriculoatrial interval, and decreased systolic blood pressure after the initiation of arrhythmia …”
Section: Discussionmentioning
confidence: 99%
“…In AVNRT, the interval is usually below 70 ms, affecting only the QRS complex. 20 The most probable explanation of the findings In our study group, the myocardial ischemia was unlikely to occur, due to the short-lasting arrhythmia paroxysms, relatively young age of the subjects and lack of patients' complaints. In AVNRT, the overlapping of retrograde P waves could not be explained.…”
Section: Discussionmentioning
confidence: 66%
“…This is why in AVNRT its influence alter rather the shape of the QRS complex – the descending arm of the R wave and the S wave than the ST segment. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is usually not visible. [9] Therefore, the most likely explanation for ST-segment depression is related to the overlapping of the individual components of the heart cycle with a sufficiently rapid tachycardia cycle. Thus, the T wave overlaps with the following QRS complex raising the baseline in front of the QRS complex, which results in the visual appearance of ST segment depression.…”
Section: Introductionmentioning
confidence: 99%